Mechanosensing of DNA bending in a single specific protein-DNA complex - Le, Shimin (2014)
Many crucial biological processes are regulated by mechanical stimuli. Here, we report new findings that pico-Newton forces can drastically affect the stability of the site-specific DNA binding of a single transcription factor, the E. coli integration host factor (IHF), by stretching a short ~150 nm DNA containing a single IHF binding site. Dynamic binding and unbinding of single IHF were recorded and analyzed for the force-dependent stability of the IHF-DNA complex. Our results demonstrate that the IHF-DNA interaction is fine tuned by force in different salt concentration and temperature over physiological ranges, indicating that, besides other physiological factors, force may play equally important role in transcription regulation. These findings have broad implications with regard to general mechanosensitivity of site-specific DNA bending proteins.